A Supply Chain Optimization Model for an Enterprise Based on Maximizing the Economic Effect - Mark A. Gorskiy; Mikhail A. Khalikov; Denis A. Maximov (International Journal of Supply Chain Management, 2020)
Abstract— This paper is motivated by the importance of addressing the challenges faced by supply chain systems in the presence of multiple uncertain factors. It focusses on three crucial areas of innovative supply chain optimization models, including supply chain operations processes, competition and interactions in supply chains, and supply chain contracting and coordination. The authors propose to separate into stages the process of determining the elemental composition of a production system (groups of technological equipment) and the sequence of these elements providing the technological process at its individual stages. At the first stage, it is proposed to use the structural-parametric optimization of the production system of the enterprise, and at the second to use the combinatorial optimization. The main result of the paper is the formulation and proof of a theorem on the relation of structurally-parametric and combinatorial supply chain optimization model.